Global wine markets, 1860 to 2016 : a statistical compendium - Anderson, Kym; Nelgen, Signe; Pinilla, Vicente, 1959- (Adelaide : The University of Adelaide Press, 2017)
Until recently, most grape-based wine was consumed close to where it was produced, and mostly that was in Europe. The latest globalization wave has changed that forever. Now more than two-fifths of all wine consumed globally is produced in another country. Europe's dominance of global wine trade has been diminished by the surge of exports from the Southern Hemisphere and the United States. Asia has emerged as an important consuming region, and in China that has stimulated the development of local production that, in volume terms, already rivals that of Argentina, Australia, Chile and South Africa. This latest edition of global wine statistics not only updates data to 2016 but also adds another century of data. The motivation to assemble those historical data was to enable comparisons between the current and the previous globalization waves. This unique database reveals that, even though Europe's vineyards were devastated by vine diseases and the pest phylloxera from the 1860s, most 'New World' countries remained net importers of wine until late in the nineteenth century. Some of the world's leading wine economists and historians have contributed to and drawn on this database to examine the development of national wine market developments before, during and in between the two waves of globalization. Their initial analyses cover all key wine-producing and -consuming countries using a common methodology to explain long-term trends and cycles in national wine production, consumption, and trade. They are available in Wine Globalization: A New Comparative History, edited by Kym Anderson and Vicente Pinilla (Cambridge University Press, February 2018).
Title from publisher's bibliographic system (viewed on 02 Aug 2018).
Keywords: Wine industry and globalization; International trade -- Case studies; Globalization -- Economic aspects -- Case studies